Intersection of Diet, Health, and Environment: Land Grant Universities' Role in Creating Platforms for Sustainable Food Systems - Ringling, Keagan M.; Marquart, Len F. (Frontiers in Sustainable Food Systems, 2020)
Food and agriculture professionals strive to feed the growing population diets that maintain human health and minimize environmental impacts. Recently, global organizations such as the World Health Organization and the Food and Agricultural Organization have set goals related to the sustainable production of nutritious foods. In this vein, the EAT-Lancet Commission on Food, Planet, and Health has set dietary recommendations for human and planetary health. These recommendations, based on a wide body of evidence, suggest that plant-based diets are essential for the persistence of the population and the environment. This article briefly reviews the influence of diets on health and environmental outcomes in the context of the EAT-Lancet recommendations. Then the brief discusses the role of land grant universities in developing nutrition sensitive, environmentally resilient food systems. Then the article discusses local food system initiatives in Minnesota and offers insight into how the University of Minnesota may play a role in developing nutrition sensitive value chains by coordinating and supporting local food efforts. Ultimately, this brief suggests that land grant universities can help local communities equitably collaborate with upstream and downstream value chain actors to develop nutrition sensitive, environmentally resilient value chains.